Telocytes in the human kidney cortex - Qi, Guisheng (J Cell Mol Med, 2012)
Renal interstitial cells play an important role in the physiology and pathology of the kidneys. As a novel type of interstitial cell, telocytes (TCs) have been described in various tissues and organs, including the heart, lung, skeletal muscle, urinary tract, etc. (www.telocytes.com). However, it is not known if TCs are present in the kidney interstitium. We demonstrated the presence of TCs in human kidney cortex interstitium using primary cell culture, transmission electron microscopy (TEM) and in situ immunohistochemistry (IHC). Renal TCs were positive for CD34, CD117 and vimentin. They were localized in the kidney cortex interstitial compartment, partially covering the tubules and vascular walls. Morphologically, renal TCs resemble TCs described in other organs, with very long telopodes (Tps) composed of thin segments (podomers) and dilated segments (podoms). However, their possible roles (beyond intercellular signalling) as well as their specific phenotype in the kidney remain to be established.